2010
DOI: 10.1007/s11916-010-0145-3
|View full text |Cite
|
Sign up to set email alerts
|

New Daily–Persistent Headache Versus Tension-type Headache

Abstract: New daily-persistent headache (NDPH) and chronic tension-type headache (CTTH) are two forms of primary chronic daily headache of long duration that often are similar in their headache manifestations. NDPH distinguishes itself from CTTH and the other forms of chronic daily headache by its continuous head pain from onset. However, despite formalized criteria that specify NDPH must resemble the acute onset of a headache identical to that of CTTH, NDPH commonly has migraine features. Here, we review the available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The proportion of medication overuse in patients with NDPH was noted from 8.6% to 45.1% . In the present study, 6 (15.8%) patients overused analgesics.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…The proportion of medication overuse in patients with NDPH was noted from 8.6% to 45.1% . In the present study, 6 (15.8%) patients overused analgesics.…”
Section: Discussionsupporting
confidence: 38%
“…This was in line with our study: patients with good outcomes had a shorter duration of illness (25.8 ± 48.5 months) as compared with duration of 116.4 ± 120.9 months for patients with bad outcomes. Robbins and Crystal further divided NDPH into 3 prognostic subgroups: persisting, remitting, and relapsing‐remitting . In this study, 1 woman could be classified as the relapsing‐remitting subtype, who experienced analogous headaches 3 times.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Robbins reported bipolar spectrum patients with chronic tension-type headache as 4.5%. [31][32][33] TTH with GAD Desai SD reported among the patients with TTH 17.9% suffered from GAD. An Italian study reported that 53.4% TTH participants had anxiety and another clinical based study in America showed 17% had anxiety in chronic TTH.…”
Section: Tth With Depressionmentioning
confidence: 99%
“…Medication overuse also must be addressed because it may develop in up to half of all adult patients with NDPH. [4] Medication overuse is much less common in adolescents with NDPH. [19]…”
Section: Other Primary Headache Syndromesmentioning
confidence: 99%